The Use of Grammar Translation Method to Facilitate EFL Students in Learning Reading Subject - Sayit Abdul Karim; Putri Lisa Anggraini; Devara Aftina Putri; Metyana Setyorini; Aditama Bagus Antasari (Jurnal Sinestesia, 2023)
This article attempts to scrutinize the use of the Grammar Translation Method (GTM) as one of the teaching methods in English language teaching for EFL students. In the English language learning and teaching context, applying an appropriate teaching method for each language skill and component is necessary for EFL teachers to help their students achieve their learning goals. The present study utilized a qualitative descriptive approach to explore several important points relating to how the GTM may facilitate EFL learners in learning reading subjects. The data were obtained from previous research findings, and documentation studies, and further analyzed qualitatively. Facilitating students’ learning needs will motivate EFL learners to actively participate in their learning activities. Therefore, the present study discusses a brief of GTM, the development of GTM, the purposes of using GTM, the technique of using GTM, the benefit of GTM, and last but not least the implication of GTM for EFL students in learning reading subject in the classroom setting. Finally, some necessary points from the perspectives of GTM are highlighted in the conclusion and suggestion part.